Nigerian petroleum business : a handbook - Eromosele, Victor E. (Lagos, Nigeria : Advent Communications Limited (for Oil & Gas Readings Group), 1997)
A handbook on the Nigerian petroleum business. It is structured in such a way that there is material for the prospective investor and financier, for the oil trader, for the oil industry manager, for the corporate planner, for the accountant and financial adviser, and for the academic.
A collection of 39 essays, with a glossary of terminology added.
Includes bibliographical references and index.
oif 06/02/2015, aia 03/05/2018
Loans
Keywords: Petroleum industry and trade; Nigeria